2019
DOI: 10.1016/j.celrep.2019.04.109
|View full text |Cite
|
Sign up to set email alerts
|

Three Types of Functional Regulatory T Cells Control T Cell Responses at the Human Maternal-Fetal Interface

Abstract: Highlights d Three decidual Treg types suppress Teff responses in human pregnancy d Decidual PD1 HI Tregs suppress T cell proliferation in an IL-10dependent manner d EVTs and decidual macrophages directly increase FOXP3+ Tregs, while EVTs also increase PD1 HI Tregs d Induction of PD1 HI Tregs by EVTs may involve antigenspecificity for HLA-C

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
161
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(172 citation statements)
references
References 58 publications
8
161
0
Order By: Relevance
“…58,59,63,123 Very recently, three types of functional regulatory T cells were identified at the human maternal-fetal interface, of which the CD25 hi FOXP3 + population matches the here studied population. 116 Decidual CD25 hi FOXP3 + Tregs effectively suppressed CD4 + and CD8 + T cell proliferation and IFN⍰ and TNF⍰ production. Transcripts identified by qPCR array as specific for this subset were IL2RA, FOXP3, TIGIT, CD39, LRRC32, ST2, BATF, and CCR8, as well as increased expression of CCR5, IL10, and GITR compared to blood Tregs, 116 which confirms our findings of an activated Treg phenotype at the maternal-fetal interface.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…58,59,63,123 Very recently, three types of functional regulatory T cells were identified at the human maternal-fetal interface, of which the CD25 hi FOXP3 + population matches the here studied population. 116 Decidual CD25 hi FOXP3 + Tregs effectively suppressed CD4 + and CD8 + T cell proliferation and IFN⍰ and TNF⍰ production. Transcripts identified by qPCR array as specific for this subset were IL2RA, FOXP3, TIGIT, CD39, LRRC32, ST2, BATF, and CCR8, as well as increased expression of CCR5, IL10, and GITR compared to blood Tregs, 116 which confirms our findings of an activated Treg phenotype at the maternal-fetal interface.…”
Section: Discussionmentioning
confidence: 98%
“…116 Decidual CD25 hi FOXP3 + Tregs effectively suppressed CD4 + and CD8 + T cell proliferation and IFN⍰ and TNF⍰ production. Transcripts identified by qPCR array as specific for this subset were IL2RA, FOXP3, TIGIT, CD39, LRRC32, ST2, BATF, and CCR8, as well as increased expression of CCR5, IL10, and GITR compared to blood Tregs, 116 which confirms our findings of an activated Treg phenotype at the maternal-fetal interface. A previously published study investigating chemokine receptor expression of CXCR3, CCR4, and CCR6 in decidual Tregs by flow cytometry, showed that CCR6 − CXCR3 + Th1 cells were increased, CCR6 + CCR4 + Th17 cells were nearly absent, whereas CCR4 + Th2 frequencies were similar in blood and decidua, 58 which is also in line with our findings.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In parallel with the above classifications, other authors have adopted similar approaches to investigate Treg cell subpopulations using markers such as CD161, CD45RO, CD39, CD49d, programmed death‐1, T‐cell immunoreceptor with Ig and ITIM domain (TIGIT), and T‐cell immunoglobulin and mucin domain 3 (TIM‐3) to elucidate subpopulation‐level heterogeneity . (Figure ) Establishing mechanistically relevant links between these subpopulations, their markers and FOXP3 (or other transcription factors) is further complicated by the fact that non‐FOXP3‐expressing T cells can be induced or genetically modified to express FOXP3 and adopt Treg‐like functions too .…”
Section: Heterogeneity Of Treg Cellsmentioning
confidence: 99%
“…Mass cytometry has been applied to study also the fluctuations in blood immune cells throughout pregnancy (23,24). Multiple populations of innate lymphoid cells (9,21,25), regulatory T cells (26), and macrophages (27) compose the diverse immune cell landscape operating at the maternalfetal interface, which varies during the stages of pregnancy and it is therefore difficult to decipher precisely. New technology such as three-dimensional organoid cell cultures (28) may help to determine some of the mechanisms underlying placentation (29).…”
Section: New Concepts and Recent Progress In The Fieldmentioning
confidence: 99%